1984
DOI: 10.21273/jashs.109.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BA, GA4+7, and Daminozide on Fruit Set, Fruit Quality, Vegetative Growth, Flower Initiation, and Flower Quality of ‘Golden Delicious’ Apple

Abstract: Five repeat spray applications at full bloom (FB) + 11 days through FB + 61 days of 50 ppm 6-benzylamino purine (BA) and/or gibberellins A4+7 (GA4+7) were made on limbs receiving 0 or 2000 ppm butanedioic acid mono-(2,2-dimethylhydrazide) (daminozide) at FB + 11 days. Similar repeat applications of BA and GA4+7 were made at FB + 4 through FB + 57 days on limbs where all blossom clusters were removed at FB or all blossom clusters were retained. GA4+7 depressed flower bud formation, whereas BA not only increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Gibberellin activity appears to increase in apple seeds 5 to 7 weeks after bloom (Ebert and Bangerth, 1981;Hoad, 1978;Luckwill, 1969), when exogenous application of gibberellins has a diminished inhibitory effect on flowering. These data support the suggestion of others (Ebert and Bangerth, 1981;Looney and Pharis, 1986;Marino and Greene, 1981;McLaughlin and Greene, 1984) that there is a poor relationship between the time the gibberellin content of seeds rises and the time when gibberellins most effectively inhibit flowering. Hoad (1978) has shown that movement of gibberellins from seeds, rather than the gibberellin content of the seeds per se, is correlated with biennial bearing.…”
Section: Concentration and Number Of Applications Ga4 7 Increased Fru...supporting
confidence: 90%
See 2 more Smart Citations
“…Gibberellin activity appears to increase in apple seeds 5 to 7 weeks after bloom (Ebert and Bangerth, 1981;Hoad, 1978;Luckwill, 1969), when exogenous application of gibberellins has a diminished inhibitory effect on flowering. These data support the suggestion of others (Ebert and Bangerth, 1981;Looney and Pharis, 1986;Marino and Greene, 1981;McLaughlin and Greene, 1984) that there is a poor relationship between the time the gibberellin content of seeds rises and the time when gibberellins most effectively inhibit flowering. Hoad (1978) has shown that movement of gibberellins from seeds, rather than the gibberellin content of the seeds per se, is correlated with biennial bearing.…”
Section: Concentration and Number Of Applications Ga4 7 Increased Fru...supporting
confidence: 90%
“…Gibberellins do not normally increase fruit size at harvest unless very high rates are used (Dennis, 1986). However, multiple applications of GA4 i 7 at 25 m g -lite r 1 starting 11 days after full bloom increased fruit size of 'Golden Delicious' (McLaughlin and Greene, 1984). Fruit size may be positively correlated with seed number (Williams and Edgerton, 1981), and developing seeds are rich sources of gibberellins (Hoad, 1978).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…McLaughlin and Green recently investigated the interacting effects of daminozide with BA and GA4+7 on apple growth and flowering (11).…”
mentioning
confidence: 99%
“…Since BA can increase flowering and lat eral branching and reduce biennial bearing in apple (3,5), it has potential for commer cial use in fruit production. Although a pre suensis crosses.…”
mentioning
confidence: 99%